Insight of Malaysian users of cosmetic regarding cosmetovigilance - Ab. Hadi, Hazrina; Jamshed, Shazia Qasim; Awadh, Ammar Ihsan Jawad; Zamli, Mazlina; Ai, Nur'ain (MDPI AG, 2020)
Despite high popularity and demand for cosmetic products among users of cosmetics, there is paucity of work on cosmetovigilance. The objective of this study was to explore the cosmetovigilance-related insight encompassing the knowledge, practices, attitude, and perception of Malaysian users of cosmetics. A cross-sectional study was conducted using a structured questionnaire comprising of 47 items reflecting on demographic profile, knowledge, practices, attitude, and perception toward cosmetics. The questionnaire was administered using the SurveyMonkey website, subject to a convenience sample of 552 users of cosmetics in Malaysia. The data collected were analyzed using the Statistical Package for Social Sciences (SPSS) version 20. Insufficient knowledge of cosmetic safety was found, especially in terms of the ingredients used and the adverse effects related to common cosmetic products. The total knowledge score showed a significant difference between gender (P < 0.001) and monthly expenditure (P = 0.001). The total attitude score showed a significant difference with respect to gender (P = 0.008), age (P < 0.001), marital status (P < 0.001), education (P = 0.014), occupation (P < 0.001), income range (P = 0.009) and monthly expenditure (P = 0.013). The levels of cosmetovigilance-related knowledge, practices, attitude and perception of users of cosmetics in Malaysia are still unsatisfactory. The current research is expected to offer baseline data which can further help in strengthening the knowledge and attitudes of cosmetic consumers, while reinforcing best practices towards cosmetic products.